Design and modeling of a Laue lens for radiation therapy with hard x-ray photons. (7th December 2021) - Girou, David; Ford, Eric; Wade, Colin; van Aarle, Casper; Uliyanov, Alexei; Hanlon, Lorraine; Tomsick, John A; Zoglauer, Andreas; Collon, Maximilien J; Beijersbergen, Marco W; Barrière, Nicolas M
Abstract: We have designed and modeled a novel optical system composed of a Laue lens coupled to an x-ray tube that produces a focused beam in an energy range near 100 keV ( λ = 12.4 picometer). One application of this system is radiation therapy where it could enable treatment units that are considerably simpler and lower in cost than present technologies relying on linear accelerators. The Laue lens is made of Silicon Laue components which exploit the silicon pore optics technology. The lens concentrates photons to a small region thus allowing high dose rates at the focal area with very much lower dose rates at the skin and superficial regions. Monte Carlo simulations with Geant4 indicate a dose deposition rate of 0.2 Gy min −1 in a cylindrical volume of 0.7 mm diameter and 10 mm length, and a dose ratio of 72 at the surface (skin) compared to the focus placed 10 cm within a water phantom. Work is ongoing to newer generation crystal technologies to increase dose rate.